2019
DOI: 10.2134/cftm2019.01.0010
|View full text |Cite
|
Sign up to set email alerts
|

Removing Peanut Foliage Adjacent Shallow Subsurface Drip Laterals to Reduce Rodent Damage

Abstract: Removal of peanut foliage in alternate row middles with an 8-or 16-inch gap did not decrease yield or grade of peanut.• There was no difference in the amount of foliage removed with either the 8-or 16-inch cut gap.• Rodent damage decreased as cut gap increased from 8-to 16-inch cut gap. AbstractUsing Shallow SubSurface Drip Irrigation (S3DI) in field crops has been successful from a yield and economic standpoint. However, the use of S3DI in peanut has been discouraging due to the amount of rodent damage to dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…There is substantial anecdotal evidence that rodent activity is further increased if crop residue is left on the soil surface, which results in a more favorable rodent habitat. As stated earlier (Sorensen, 2019), removal of peanut foliage resulted in reduced rodent damage to SDI driplines. At the USDA-ARS laboratory in Bushland, Texas, nearly 50 labor h ha -1 was needed to repair SDI driplines after fallowing with wheat stubble in the previous summer, fall, and winter.…”
Section: Challenges and Opportunities For Sdi Maintenancesupporting
confidence: 54%
See 1 more Smart Citation
“…There is substantial anecdotal evidence that rodent activity is further increased if crop residue is left on the soil surface, which results in a more favorable rodent habitat. As stated earlier (Sorensen, 2019), removal of peanut foliage resulted in reduced rodent damage to SDI driplines. At the USDA-ARS laboratory in Bushland, Texas, nearly 50 labor h ha -1 was needed to repair SDI driplines after fallowing with wheat stubble in the previous summer, fall, and winter.…”
Section: Challenges and Opportunities For Sdi Maintenancesupporting
confidence: 54%
“…The economic longevity of S 3 DI was estimated to be approximately 5.4 years (i.e., cost to repair leaks equal to replacement cost) by Sorensen and Lamb (2015) for a cottoncorn-peanut rotation in Georgia. Further work at this location to improve S 3 DI longevity found that removal of peanut foliage above the dripline greatly decreased the amount of rodent damage without reducing peanut yield or grade (Sorensen, 2019). Removal of residue with tillage has also been anecdotally reported to reduce rodent damage to driplines in many other regions of the U.S. A much deeper (0.40 to 0.45 m) SDI system on a deep silt loam soil in Kansas had a system life of 26.5 years without replacement (Lamm and Rogers, 2017).…”
Section: Studies Of Sdi Responses And/or Performance Improvements For Grain and Oilseed Cropsmentioning
confidence: 99%
“…This could be partly explained by the fact that we reproduced only subsurface conditions, considering the relevance of SDI in the Mediterranean Basin due to the efficient water use, reduced energy costs and protection from weather conditions that this system ensures [68,69]. It is known that SDI systems in other areas may be strongly damaged by rodents [29,70], while surface systems such as microsprinklers or SD are vulnerable to birds and different chewing mammals [71][72][73]. Therefore, new tests in other areas and/or using surface systems would be highly advisable to determine whether our method can simultaneously control ants and larger agents, which is one of its main potential advantages compared to traditional approaches.…”
Section: Discussionmentioning
confidence: 99%